Suitability of using compacted granite residual soil treated with palm oil fuel ash as hydraulic barrier in sanitary landfill - Muhammed, Abubakar Sadiq (2015)
Modern landfills employ a composite liner system consisting of a geomembrane or geosynthetic clay liner overlying a compacted soil liner. For soils either natural or mixed with additive to satisfy the requirement of a liner, it must have low hydraulic conductivity, adequate shear strength and minimal shrinkage. An experimental investigation was conducted on granite residual soil treated with up to 15% palm oil fuel ash (POFA) to assess its suitability for liners in waste containment systems. Soil samples were prepared at moulding water content ranging from -2, 0, +2 and +4% of the optimum moisture content (OMC) and compacted with two compactive energy levels (standard and modified proctor). The tests carried out were divided into physical (moisture content, specific gravity, sieve analysis, Atterberg limit compaction), chemical (cation exchange capacitymineral composition, chemical oxides, structural morphology, elemental composition of leachate) and mechanical properties (hydraulic conductivity, volumetric shrinkage strain, unconfined compressive strength, compatibility studies) of both the natural soil and the mixture with POFA. Specific surface area was carried out on the POFA sample. The optimum properties of the soil mixture were then tested by carrying out the compatibility study. Compatibility study, which is the interaction between the leachate and the barrier material was determined based on the short – time hydraulic conductivity test using the leachate as the permeant. The concentrations of heavy metals contain in leachate before and after test were also assessed. The results of the index properties of soil and soil – POFA mixture carried out provided a useful way to identify, classify and assess the engineering properties of the soil.The natural soil contained 53.13% fine content and that value increased to 59.14% with 15% POFA content. The index properties of samples met the minimum requirement for it to be used as a liner. Soils with high fine content have smaller particles that reduce the volume of voids present allow less hydraulic conductivity and also higher liquid limit are related to lower hydraulic conductivity. Chemical composition of POFA showed a fair result of 67.80% in comparison to the minimum requirement of 70% for pozzolanic reaction as stated by ASTM. While on the otherhand, the addition of POFA showed a modification in the structure of the soil from a porous to a dense structure. The maximum dry density and optimum moisture content decreased and increased respectively for both compactive efforts. For both compactive energies, the hydraulic conductivity generally decreased with increase in moulding water content, the lowest were obtained at the wet side of the compaction curve especially at +2% of the optimum moisture content. At modified proctor compactive effort and +2% of the OMC, hydraulic conductivity values of 6.51×10-9, 2.23×10-10, 2.31×10-11 and 1.31×10-9m/s were obtained at 0, 5, 10 and 15% POFA, respectively. However, beyond +2% of the OMC, there was a slight increase in hydraulic conductivity values. For the volumetric shrinkage strain (VSS), there was increase in VSS values with higher moulding water content and also at higher initial degree of saturation for all compactive efforts. The largest VSS value of 5.91% was obtained at soil containing 15% POFA and +4% of the OMC. The influence of POFA treatment generally showed a decrease in the VSS with the increase in POFA content. On the other hand, shear strength values increased with the addition of POFA and at higher compactive effort, with the highest strength recorded at 10% POFA using modified proctor compactive effort. However, the values decreased at higher moulding water content irrespective of POFA content and compactive effort. Based on the acceptable zone on the compaction plane, 10% POFA gave the widest range ofmoulding water content in which minimumset of values based on the hydraulic conductivity, shear strength and volumetric shrinkage were achieved. For a compatibility study, results showed that there was a general decrease in hydraulic conductivity values at different percentages of POFA, with the highest reduction rate of 65.4% recorded at 10% POFA mixture. This could be as a result of suspended solids in the leachatewhich were absorbed at the surface of the soil there by reducing percolation with time. On the other hand the concentration of some metals was drastically reduced when permeated through the compacted material.